2013
DOI: 10.1186/1471-2474-14-177
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic venous thromboembolism and mortality in orthopaedic surgery – an observational study of 45 968 consecutive procedures

Abstract: BackgroundLittle information exists on the presentation of symptomatic venous thromboembolism (VTE) in orthopaedic surgery when a defined protocol for thromboprophylaxis is used. The objective with this study was to establish the VTE rate and mortality rate in orthopaedic surgery.MethodsWe performed a prospective, single centre observational cohort study of 45 968 consecutive procedures in 36 388 patients over a 10 year period. Follow-up was successful in 99.3%. The primary study outcome was the incidence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 42 publications
2
80
2
Order By: Relevance
“…This is comparable to larger-scale studies that reported clinically symptomatic DVT incidences of 2.1%, 2.8% and 3.7% for patients who underwent arthroplasty. (9,12,13) However, the patients in those studies had both mechanical and chemical thromboprophylaxis, while the patients in the present study only had mechanical prophylaxis.…”
Section: Discussionmentioning
confidence: 46%
“…This is comparable to larger-scale studies that reported clinically symptomatic DVT incidences of 2.1%, 2.8% and 3.7% for patients who underwent arthroplasty. (9,12,13) However, the patients in those studies had both mechanical and chemical thromboprophylaxis, while the patients in the present study only had mechanical prophylaxis.…”
Section: Discussionmentioning
confidence: 46%
“…62, 184 The majority of VTE occurred following discharge, which has also been previously reported in the literature. 51,62,143,184,185 As all readmissions to hospital for VTE treatment were under medical units, local VTE incidence following arthroplasty may be underestimated by surgical teams.…”
Section: Discussionmentioning
confidence: 99%
“…85,88 Interestingly, the type of anaesthesia may also infuence VTE risk: regional anaesthesia has been reported to carry a lower VTE risk than general anaesthesia; consequently it is often recommended in guidelines and commonly used in practice. 17,51,89,90 A recent study reported that East Asian patients experience very little to no symptomatic VTE following hip and knee arthroplasty, suggesting the value of using routine thromboprophylaxis is debatable in East Asia. 81 Notably, studies in South East Asia have actually reported higher symptomatic VTE rates to other studies (5.1%).…”
Section: Other Influencing Factorsmentioning
confidence: 99%
See 2 more Smart Citations